2021
DOI: 10.1111/aab.12707
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between agronomic traits, soil properties and essential oil profile of peppermint (Mentha piperita L.) treated by fertiliser treatments and irrigation regimes?

Abstract: One of the greatest challenges in recent years is providing enough food to feed the increasing world population, with limited freshwater resources. However, effective fertiliser management also has a fundamental role to improve yield quality and quantity. Organic fertiliser not only supplements nutrients but also improves physicochemical and biological soil properties. A 2-year field experiment was conducted to examine the influence of urea and vermicompost fertiliser on oil phytochemical properties of pepperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In general, when the level of stress was increased from 2.5 to 7.5 dS m −1 , the concentration of MDA in all the species increased, thus indicating the severe destruction of the cell membranes of these species. Biotic stress, as a result of an increase in the production ROS, can play an important role in lipid peroxidation [7] . Other researchers have reported an increase in the MDA concentration of leaves, due to salinity stress, in mint, [6] basil, [37] and sage [38] .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In general, when the level of stress was increased from 2.5 to 7.5 dS m −1 , the concentration of MDA in all the species increased, thus indicating the severe destruction of the cell membranes of these species. Biotic stress, as a result of an increase in the production ROS, can play an important role in lipid peroxidation [7] . Other researchers have reported an increase in the MDA concentration of leaves, due to salinity stress, in mint, [6] basil, [37] and sage [38] .…”
Section: Resultsmentioning
confidence: 97%
“…Biotic stress, as a result of an increase in the production ROS, can play an important role in lipid peroxidation. [7] Other researchers have reported an increase in the MDA concentration of leaves, due to salinity stress, in mint, [6] basil, [37] and sage. [38] They stated that the destruction of cell membranes, under the influence of salinity stress, and the production of leaf MDA, due to the degradation and breakdown of cell membrane lipids, could be considered as a suitable criterion to study the response of plants to salinity stress.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…3 ). Keshavarz Mirza Mohammadi et al ( 2021b ) observed that the production of phenolic compounds in the peppermint had little variation throughout the year, despite significant differences in air temperature were observed in different months. Results demonstrated that drought stress treatment decreased the content of total phenolics than well-watered (control) treatment by 25.7% (Fig.…”
Section: Resultsmentioning
confidence: 99%